Veneration of the Buddhist Canon and National Integration in the Yuan Dynasty: Religious Policy and Cultural Convergence - Xiaobai Li (Religions, 2025)
Inheriting a tradition of religious tolerance from the Inner Asian Steppe, the Mongol Yuan Empire elevated Buddhism to a pivotal role in unifying its multiethnic and culturally diverse domain, with Tengriist ideology serving as the political foundation for these Buddhist veneration policies. The ruling class of the Yuan dynasty practiced a complex interaction between religion and political unity through the institutionalization of the cult of writing, printing, and reading the Buddhist Canon. Specifically, the Yuan dynasty established specialized government offices to mobilize elites from Mongolian, Han Chinese, Goryeo, and other ethnic groups for the construction of a multilingual Buddhist Canon. They copied the scriptures with gold and silver ink in Chinese, Tibetan, Uyghur, and other languages. Participants in scripture copying were rewarded or granted official positions. In this way, they achieved the goal of enlisting local elites, the cohesion of the community’s beliefs, and enhanced the unity of the local elites. By subsidizing the writing and reading of Buddhist classics, the Yuan rulers succeeded in constructing a space of identity at the level of material culture and facilitated cultural interaction and political integration among various social groups such as the Mongols, ethnic groups, and Han Chinese. Through state-sponsored scripture carving and recitation activities, the Yuan rulers cultivated a shared identity in the material culture sphere, facilitating cultural exchange and political integration across the Mongolians, the Han Chinese, and other ethnic communities. However, the effectiveness of state unification was significantly constrained by the Mongolian rulers’ policy of ethnic segregation, central–local conflict, and the high concentration of social wealth in the Buddhist communities.